Troubles which class teachers in primary education encounter in new science and technology teaching program - Ugras, Mustafa; Cil, Erol (Elsevier Science Bv, 2012)
The new science and technology teaching program was started to apply in 2006 in Turkey. Since then, teachers have discussed on the new science and technology teaching program. This study was performed to determine the troubles which class teachers in primary education encounter in new science and technology teaching program. For this purpose; a survey, developed by Erdem and named as Science and Technology Teaching Program Problem Scale, was applied to 4th and 5th class teachers in Elazig in Turkey. The participants of this research included 244 class teachers who were teaching 4th and 5th class in 38 different elementary schools in 2010-2011 academic years. The results of the survey were considered by using SPSS packet program. In the analyzing of data obtained from this study, frequency, arithmetic average, t-test and variance analysis were used. From the obtained data, it was determined that the 4th and 5th class teachers encounter different problems in science and technology teaching program, especially in performance homework, sourcing and lesson time topics.
Cyprus International Conference on Educational Research (CY-ICER) -- FEB 08-11, 2012 -- Middle E Tech Univ No Cyprus Campus, CYPRUS
Keywords: Science and Technology Course; Instruction Curriculum; Teacher Opinions